Orally Administered Probiotics Decrease Aggregatibacter actinomycetemcomitans but Not Other Periodontal Pathogenic Bacteria Counts in the Oral Cavity: A Systematic Review and Meta-Analysis - Sang-Ngoen, Thanyaporn; Czumbel, László Márk; Sadaeng, Wuttapon; Mikó, Alexandra; Németh, Dávid István; Mátrai, Péter; Hegyi, Péter; Tóth, Barbara; Csupor, Dezső; Kiss, István; Szabó, Andrea; Gerber, Gábor; et al. (Frontiers in Pharmacology, 2021)
Introduction. At the initial part of the gastrointestinal tract, multiple tissues serve the normal function of food delivery. Periodontal structures are integral elements of these. When they have deteriorated, it is extremely challenging to regenerate and reconstruct them. The conventional intervention for periodontal disease is scaling and root planning with the aim of reducing pathogenic bacteria. However, periodontal pathogens can rapidly re-colonize treated areas. Probiotics have been proposed as novel tools for managing oral health by suppressing pathogenic bacteria through their anti-inflammatory effect, but the available data are controversial. Aim. Therefore, we performed a meta-analysis to study the effect of probiotics on periodontal pathogenic bacteria. Methods. The study was registered in PROSPERO under registration number CRD42018094903. A comprehensive literature search from four electronic databases (PubMed, Cochrane CENTRAL, Embase and Web of Science) yielded nine eligible records for statistical analysis. Studies measuring bacterial counts in saliva, and supra- and subgingival plaque were included. Bacterial counts were analysed using standard mean difference (SMD) and applying a random effects model with the DerSimonian–Laird estimation. Results. The results showed a significant decrease in the overall count of Aggregatibacter actinomycetemcomitans in the probiotics-treated group compared to control at 4 weeks (SMD: -0.28; 95% CI: -0.56–-0.01; P=0.045) but not later. Analysing the bacterial counts in subgroups, namely in saliva, and supra- and subgingival plaque separately, yielded no significant difference. Probiotics had no significant effect on the overall count of Porphyromonas gingivalis at 4 weeks (SMD: -0.02; 95% CI: -0.35–0.31; P=0.914) or later. Subgroup analysis also revealed no significant difference between treatment and control groups, nor did probiotics significantly decrease the overall and subgroup bacterial counts of Prevotella intermedia, Tanellera forsythia and Fusobacterium nucleatum. Conclusion. Our data support the beneficial effect of probiotics in reducing A. actinomycetemcomitans counts, but not of other key periodontal pathogenic bacteria in periodontitis patients. However, due to the complex mechanism associated with periodontal disease and the limitations of the available studies, there is a furthe